Psychological assessment and the role of the psychologist in early palliative care - Iannizzi, Pamela; Feltrin, Alessandra; Martino, Rosalba; De Toni, Chiara; Galiano, Antonella; Pambuku, Ardi; Nardi, Mariateresa; Meraviglia, Nicla; Brunello, Antonella; Zagonel, Vittorina (Frontiers in Psychology, 2024)
Background: Early palliative care (EPC) is a care model recommended for improving quality of life of patients in advanced cancer and caregivers. Few studies have deepened the role of psychological evaluation in EPC. Veneto Institute of Oncology (IOV) is a Comprehensive Cancer Centre in which patients with advanced-stage disease are evaluated by an interdisciplinary team. This study aims to: assess the psychological needs in these patients; assess any correlations between the psychological symptoms (PSs) and the awareness of diagnosis and prognosis, symptoms detected by Edmonton Symptom Assessment System (ESAS), the patient's gender, age, social problems, and survival; define the role of psychologist within the interdisciplinary team.Methods. Data were retrieved from the prospectively maintained database. From January 1, 2018 to December 31, 2021, 819 consecutive patients were evaluated at EPC consultation, and 753 enrolled in the study. The ESAS was administered to each patient before the consultation.Results. More than half of the patients (385, 57.1%) reported at least one PS with an ESAS score ≥ 4: depression was reported by 34.9% of the patients, anxiety by 28.7%, and "not being well" by 43.2% of the sample. Referring oncologists tend to overestimate the presence of PSs compared to patient self-reports (51.8% versus 41.3%). According to the psychologists' assessment, depression was found in 29.2% and anxiety in 10.8% of the subjects. Thirty-one patients (10.8%) with psychological disorders had an adaptation disorder linked to a physical condition. Forty-seven percent of patients were taken in by the psychology service, and 18.5% of patients refused psychological support.Patients with other ESAS symptoms ≥ 4 increased the odds ratio to present the PSs ≥ 4. Multivariable analysis showed no relations between PSs and awareness of diagnosis and prognosis.Conclusions Systematic use of self-assessment in EPC is crucial to learn about the patient's experience and to determine whether PSs are secondary to physical disorders and to prioritize intervention. Awareness of the prognosis does not increase anxiety and depression in the patients, therefore EPC is an ideal opportunity to discuss prognosis and help the patient in an early sharing of end-of-life choices.